2013
DOI: 10.5665/sleep.3056
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Lifestyle Interventions on Obstructive Sleep Apnea (OSA): Systematic Review and Meta-Analysis

Abstract: Published evidence suggests that weight loss through lifestyle and dietary interventions results in improvements in obstructive sleep apnea parameters, but is insufficient to normalize them. The changes in obstructive sleep apnea parameters could, however, be clinically relevant in some patients by reducing obstructive sleep apnea severity. These promising preliminary results need confirmation through larger randomized studies including more intensive weight loss approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
144
1
15

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(169 citation statements)
references
References 53 publications
9
144
1
15
Order By: Relevance
“…26-31 This, in turn, may be strongly associated with future cardiovascular events, fatal arrhythmia and sudden cardiac death. 5,6,8,9,24,32,33 OSA is also a common sleep disorder associated with several adverse health outcomes, 34 and the sporadic night arousal characteristic of OSA is responsible for the nocturia. 35 In the present study, the severity of SDB correlated with the frequency of nocturnal urination; however, the mechanism of nocturia in patients with OSA has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…26-31 This, in turn, may be strongly associated with future cardiovascular events, fatal arrhythmia and sudden cardiac death. 5,6,8,9,24,32,33 OSA is also a common sleep disorder associated with several adverse health outcomes, 34 and the sporadic night arousal characteristic of OSA is responsible for the nocturia. 35 In the present study, the severity of SDB correlated with the frequency of nocturnal urination; however, the mechanism of nocturia in patients with OSA has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Since, for the snoring symptoms, a 95% significant drop in prevalence was found for the RYGB group, with no change in the NS group, it is possible to speculate that the effects on blood pressure in the S group would be related to sleep apnea since by improving it using other types of treatment, hypertensive levels of blood pressure can decrease. 20 In the same context, in the Norwegian study of Hofsø et al, 4 76 patients underwent RYGB and 63 received an NST for intensive lifestyle modifications: clear benefits of RYGB on decreasing the BP of the SO patients were shown. Rossi et al 15 also showed a similar decrease of 68.1% in cases of hypertension after surgery.…”
Section: Discussionmentioning
confidence: 97%
“…This recommendation has been bolstered by findings from large-scale clinical trials that have demonstrated improvement of OSA with interventions that incorporate calorie restricted [6][7] , or very low calorie diets [8] . Furthermore, others have reported that the magnitude of reduction in apnea-hypopnea index (AHI), a measure of OSA severity, is associated with the degree of weight loss [9][10] .…”
Section: Weight Loss For Osa Treatmentmentioning
confidence: 99%